SOLAR POWERED TRAFFIC CONTROL SYSTEM BASED ON TRAFFIC DENSITY WITH EMERGENCY VEHICLE ALERT - Bajirao Patil; Matin Sayyed; Sahil Jadhav; Yash Vedapathak; Prof. Jadhav V. V. (International Journal of Innovations in Engineering Research and Technology, 2023)
Traffic lights play such an important role in traffic management to control the traffic on the road. Situation at traffic light area is getting worse especially in the event of emergency cases. During traffic congestion, it is difficult for emergency vehicle to cross the road which involves many junctions. This situation leads to unsafe conditions which may cause accident. Traffic police gave authority to emergency vehicle driver to activate the traffic light remotely is developed and designed to help emergency vehicle crossing the road at traffic signal during emergency situation. This system used Peripheral Interface Controller (PIC) to program a priority based traffic light controller for emergency vehicle. During critical cases, emergency vehicle such as ambulance can activate (trigger) the traffic light signal to change from red to green that’s to make clearance for its path automatically. By help of Radio Frequency (RF) the traffic light will turn back to its normal operation when the ambulance finishes crossing the road.